Brand Knowledge and Organizational Loyalty as Antecedents of Employee-Based Brand Equity: Mediating Role of Organizational Culture - Liu, Xiaoming (Frontiers in Psychology, 2022)
This study tends to explore the impact of brand knowledge and organizational loyalty under the mediating role of organizational culture on employee brand-based equity. For this purpose, employees of the hospitality sector were contacted to collect data through personally administrated questionnaires. Already established scales were used to devise instrument. Data was collected in two waves in order to minimize the common method biasness. In the first wave total of six hundred questionnaires were floated, out of which four hundred were received back. A secret identification code was allotted to each questionnaire, so that the respondents could be traced easily later on in second wave. In the second wave remaining respondents were approached who have filled survey in the first wave. At this time from the floated four hundred questionnaires, only 320 were received back, from which the partially and incomplete questionnaires were discarded and at the end 306 questionnaires were left. These final and completed responses were used for the data analysis and inferential purpose in this study. Collected data has been analyzed through Structural Equation Modeling by using Smart PLS 3 software. Assessment of measurement and structural model indicated a good model fit and results indicate that employee brand based equity is influenced by organizational loyalty and brand knowledge positively. Moreover mediating role of organizational culture has also been proved.